Evaluation of Boat Lifting System Using A Multiple-Drum Winch - Asmara, I Putu Sindhu; Yudo, Hartono (Department of Naval Architecture - Diponegoro University, 2020)
Material handling equipment is designed or selected based on two factors, the aspects of technical and economic. Technical aspects of a boatlift are designated by technical specifications that can meet with the need to lift and move a boat from land to waterway and vice versa. Boatlift is a type of Rubber Tyred Gantry crane specifically designed for moving of small craft, small and medium vessels with a capacity of 10 tons to 600 tons. Boatlift with a capacity of 5 tons is very rarely to find and very different from other types of cranes such as overhead cranes that are easy to find. Boatlift with a capacity of 5 tons can be found at the Shipbuilding Institute of Polytechnic Surabaya, but it has a weakness. The boats experience an un-synchronize movement during the lifting process. This article provides the design of a boatlift pulley system with a capacity of 5 tons using a multiple-drum winch and is capable of lifting the boat at an even keel condition. The evaluation was carried out on the existing system to find the cause of the problem. The correction on the pulley system of the boatlift has been recommended without the replacement of wire rope, brakes, motor, and the multiple-drum of the winch. The weaknesses of boat lifting could be overcome by using a pulley system 8/2/2/1-DeBe + spreader.